GAMBARAN PENGGUNAAN OBAT PADA PASIEN PENYAKIT GINJAL KRONIK (PGK) YANG MENJALANI HEMODIALISIS DI RS X BEKASI PERIODE JANUARI – MARET 2020 - Prasetya, Niko; Tanty, Herty Nur; Iskandar, Honey; Pranacistri, Retnayu (Jurnal Riset Kefarmasian Indonesia, 2022)
Chronic Kidney Disease (CKD) is a condition of kidney damage that occurs for 3 months or more in the form of structural or functional abnormalities of the kidneys with or without a decrease in the Glomerular Filtration Rate. So far, treatment for CKD can be done by hemodialysis, Continuous Ambulatory Peritoneal Dialysis (CAPD) and kidney transplantation. This study aims to determine the description of the use of drugs in CKD patients undergoing hemodialysis at Hospital X Bekasi from January to March 2020. This study was conducted using a descriptive method. Sampling in January - March 2020 was carried out with the total sampling method, namely all electronic prescription sheets of CKD patients undergoing hemodialysis at Hospital X Bekasi. Data were collected by calculating the amount and percentage based on the active substance and class of drugs used by CKD patients undergoing hemodialysis. Based on the results of observations of electronic prescriptions of drugs used by CKD patients undergoing hemodialysis at Hospital X Bekasi during January - March 2020, it can be concluded that the use of drugs based on the active substance is Calcium carbonate 500 mg capsules as many as 10580 capsules (59.07%), Sodium bicarbonate 500 mg tablets 1725 tablets (9.63%), Gentamicin sulfate 80 mg/2 ml inj 868 ampoules (4.85%), Vitamin C (ascorbic acid) 200 mg/2 ml inj 753 ampoules (4.21% ), Recombinant human erythropoietin 3000 IU 678 injection (3.78%).